Behaviour of stud-to-sheathing fastener connections in LSF walls at elevated temperatures. (1st July 2021) - Abeysiriwardena, Tharindu; Peiris, Mithum; Mahendran, Mahen
Highlights: Conducted experimental studies of stud-to-gypsum plasterboard sheathing screw connections. Investigated local in-plane behaviour of stud-to-sheathing screw connections at elevated temperatures. Investigated pull-through behaviour of stud-to-sheathing screw connections at ambient and elevated temperatures. Developed characteristic curve models for nonlinear in-plane and pull-through load-displacement responses. Proposed predictive equations for elevated temperature capacity and stiffness reduction factors. Abstract: Light-gauge steel framed (LSF) walls used in low- and mid-rise buildings are usually sheathed with gypsum plasterboard to protect the thin-walled steel studs in fire. The structural failures of these walls in fire are mostly associated with local in-plane shear or pull-through failures at their stud-to-gypsum plasterboard sheathing screw fastener connections. The reductions in the mechanical properties of gypsum plasterboard and cold-formed steel studs at elevated temperatures significantly reduce the strength and stiffness provided by the stud-to-sheathing screw connections, which may lead to premature structural failure of LSF wall studs. Many detailed studies are available on the ambient temperature local in-plane response of stud-to-sheathing connections, however, the studies of both local in-plane and out-of-plane responses of stud-to-sheathing connections at elevated temperatures are limited. Therefore in this study local in-plane shear tests at elevated temperatures and pull-through tests at both ambient and elevated temperatures were conducted to determine the load–displacement behaviour, and capacity and stiffness reduction factors of stud-to-gypsum plasterboard sheathing screw connections. Suitable models of characteristic curves are also proposed to predict the in-plane and pull-through load–displacement responses of these connections at elevated temperatures. The results from this study can be used in advanced numerical analyses to optimize the design of load-bearing LSF walls under fire conditions.